Emotional intelligence (EI) and employee performance at Johor Customs Tower, Royal Malaysian Customs Department / Nilam Mizati Mohd Ismail - Mohd Ismail, Nilam Mizati (Faculty of Business and Management, 2018)
The study explored the dimensions of emotional intelligence influence on employee performance at Johor Customs Tower of Royal Malaysian Customs Department, Johor Bahru . This study was divided into five important chapters named as introduction, literature review, research methodology, findings and conclusion and recommendation. The purpose of this study is to investigate whether factor of emotional intelligence influence employee performance. This empirical study collected by using quantitative data from employee at Johor Customs Tower, 180 questionnaires were distributed and all of them has been returned. Four variables has been measured which are self-awareness, self-regulation, self-motivation and social skills. The findings show that there are significant relationship between self-awareness, self-regulation, self-motivation and social skills. towards employee performance. The findings of this study are limited to Johor Customs Tower. There are recommendations provided in every variable accepted and future research for better understanding to conduct this study in the future.